Stylistic Foregrounding in English and Uzbek Advertising Discourse (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines stylistic foregrounding in English and Uzbek advertising discourse, focusing on how creative language is used to attract and persuade audiences. Through analysis of selected advertisements, the study identifies key techniques such as metaphor, repetition, rhyme, and cultural references. English ads often favor lexical innovation and direct appeals, while Uzbek ads emphasize cultural expressions, politeness, and repetition. The findings highlight how stylistic choices reflect broader cultural values and communicative traditions. This comparative study offers insights into the role of language in advertising and contributes to cross-cultural understanding of persuasive strategies.